Aplikasi Air Kelapa yang Diperkaya Bacillus substilis B1 untuk Meningkatkan Pertumbuhan dan Hasil Tanaman Caisin (Brassica chinenchis l.) - Nindi Dyah Ayu Permata Sari; Sakhidin; Heru Adi Djatmiko (UNU Purwokerto, 2021)
This study aims to: (1) Obtain the best treatment for coconut water enriched by B. substilis B1 in increasing caisin plants' growth. (2) Getting the best treatment of coconut water enriched by B. substilis B1 in increasing caisin plants' yield. The research was carried out at the Screen House, the Laboratory of Agronomy and Horticulture, and the Laboratory of Plant Protection, Faculty of Agriculture, Jenderal Soedirman University. The experimental design used was a completely randomized block design (RAKL) with 8 types of treatment, including control treatment (P0 = 0 ml coconut water), P1 (50 ml coconut water), P2 (100 ml coconut water), P3 (150 ml coconut water), P4 (200 ml coconut water), P5 (250 ml coconut water), P6 (300 ml coconut water) and P7 (350 ml coconut water). Each treatment was repeated 4 times. The results showed that: 1) giving coconut water enriched with B. substilis B1 affected plant height. Provision of 50 ml of coconut water + 1 ml of B. substilis B1 produced the highest plants; 2) the provision of coconut water enriched with B. substilis B1 affected plant dry weight, root wet weight, and root dry weight, but not better than P0 (control).